1992
DOI: 10.1007/bf01744451
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular actions of OPC-18790: A novel positive inotropic agent with little chronotropic action

Abstract: OPC-18790 [(+/-)-6-[3-(3,4-dimethoxybenzylamino)-2-hydroxypropoxy]- 2(1H)-quinolinone], a novel positive inotropic agent, was investigated in several in vitro and in vivo experiments to elucidate its cardiovascular effects and its mechanism of action. In isolated blood-perfused dog heart preparations, OPC-18790 increased contractile force at 10 to 1,000 nmol i.a.; increased coronary arterial blood flow at 30 to 1,000 nmol; and decreased sinus rate slightly at 1,000 nmol. Atrio-ventricular nodal conduction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…We reported that the lengthening effect of class I antiarrhythmic drugs on IVCT correlated well with the antiarrhythmic potency of these drugs on digitalis and coronary ligation VTs. In an in vivo study (1), OPC 18790 decreased the AV conduction time, but had no effect on the intraventricular conduction. We do not know the reason for the discrepancy between the two results, but as judged by the high doses needed to produce these effects, they may not play a significant role in their effect on the arrhythmias.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We reported that the lengthening effect of class I antiarrhythmic drugs on IVCT correlated well with the antiarrhythmic potency of these drugs on digitalis and coronary ligation VTs. In an in vivo study (1), OPC 18790 decreased the AV conduction time, but had no effect on the intraventricular conduction. We do not know the reason for the discrepancy between the two results, but as judged by the high doses needed to produce these effects, they may not play a significant role in their effect on the arrhythmias.…”
Section: Discussionmentioning
confidence: 86%
“…OPC-18790 is a newly synthesized positive inotropic agent with vasodilator activity and reported to be devoid of digitalis-like and catecholamine-like actions (1,2). Its chemical structure, (±)-6-[3-(3,4-dimethoxybenzyl amino)-2-hydroxypropoxy]-2(1H)-quinolinone, is similar to that of vesnarinone (OPC-8212), a positive inotropic drug without vasodilating action, and phosphodiesterase (PDE) inhibiting action is one of the common positive inotropic mechanisms between the two drugs (3 5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From this point of view, toborinone may act as an IK blocker rather than a PDE III inhibitor in the sinoatrial node. In the previous study, toborinone limited the increase in sinoatrial node activity (1,4). Since E-4031 prolonged CL in the present and previous studies (10) in the sinoatrial node preparation, one possible mechanism for the lack of positive chronotropism of toborinone may be in part due to its blocking action on IK.…”
Section: Toborinone ([(±)-6-[3-(34-dimethoxybenzylamino)-2-hydroxyprmentioning
confidence: 81%
“…known as OPC-18790 in former publications) is a novel positive inotropic agent (1,2). This compound has an inhibitory action on the peak III phosphodiesterase (PDE III) of isolated heart in dogs (1) and humans (3).…”
Section: Toborinone ([(±)-6-[3-(34-dimethoxybenzylamino)-2-hydroxyprmentioning
confidence: 99%